Physicochemical characterization of native glycyl-l-histidyl-l-lysine tripeptide for wound healing and anti-aging: a preformulation study for dermal delivery. (17th February 2016) - Badenhorst, Travis; Svirskis, Darren; Wu, Zimei
Abstract: This study investigates the physicochemical properties of glycyl-histidyl-lysine-copper (GHK-Cu) to support the development of a formulation for effective topical delivery. The solubility and distribution coefficients (log D) were investigated using conventional methods and GHK concentrations were quantified with a validated stability-indicating reversed phase high performance liquid chromatography (RP-HPLC) method. In addition, the stability of GHK-Cu under stressed conditions and the compatibility with some potential formulation components were assessed. The peptide was susceptible to hydrolytic cleavage under basic and oxidative stressors and to a lesser extent acidic stress with first-order degradation profiles. Surprisingly, the peptide was stable in water and in pH (4.5–7.4) buffers for at least two weeks at 60  °C. The HPLC in conjunction with mass spectrometry identified three key degradation products, one of which was the constituent amino acid histidine. The distribution coefficients in octanol-phosphate buffered saline indicated the highly hydrophilic nature of GHK-Cu with log D values between −2.38 and −2.49 at pH range of 4.5–7.4. Furthermore, GHK-Cu was compatible with Span 60 based niosomes but less stable in the presence of the negatively charged lipid dicetyl phosphate. In summary, the preformulation studies provided information useful to deliver the GHK-Cu complex by carrier.